2006
DOI: 10.1097/01.aog.0000206777.28541.fc
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Persistence or Recurrence After Conization for Cervical Intraepithelial Neoplasia III

Abstract: II-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 15 publications
8
37
1
1
Order By: Relevance
“…The specificity of ECC is high in both groups, younger women 0.83 and older patients 0.94, whereas the positive endocervical margin showed low specificity in both groups, 0.64 and 0.56. These findings concerning the sensitivity and specificity of ECC and endocervical margin status are similar to that reported by Lu et al (8). The sensitivity of ECC was 0.581 versus 0.655 for the endocervical margin, while the specificity of ECC was 0.943 versus 0.836 for the endocervical margin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The specificity of ECC is high in both groups, younger women 0.83 and older patients 0.94, whereas the positive endocervical margin showed low specificity in both groups, 0.64 and 0.56. These findings concerning the sensitivity and specificity of ECC and endocervical margin status are similar to that reported by Lu et al (8). The sensitivity of ECC was 0.581 versus 0.655 for the endocervical margin, while the specificity of ECC was 0.943 versus 0.836 for the endocervical margin.…”
Section: Discussionsupporting
confidence: 90%
“…Lu et al (9) found incidences for residual disease in 56.5% of patients over 50 years and in 29.3% of patients younger than fifty years. An explanation for the results could be the fact that the transformation zone in older women is retracted into the endocervical canal (deep inversion) and that a progressive atrophy of the genital tract occurs in elder women (4,(7)(8)(9)(10). The sensitivity of ECC for residual CIN and/or carcinoma is low in both age groups,, 0.35 and 0.44, respectively, whereas sensitivity of a positive endocervical margin status of the cone is higher in both groups, 0.79 and 0.69, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Therefore, information concerning gland involvement should influence patient management; the option of deeper conization may have advantages over LEEP or cryotherapy to ensure negative margins for suitable patients. [18]…”
Section: Discussionmentioning
confidence: 99%
“…[3] The information concerning EGI on Pap smears may influence the decision to perform deeper conization, LEEP biopsy or cryotherapy to ensure negative margins. [18]…”
Section: Introductionmentioning
confidence: 99%
“…A positive margin or positive postprocedure endocervical sampling is a marker for increased risk of recurrence; however, only age, lesion size, and CIN grade are independent risk factors (152,153). Even with a positive endocervical margin, 70-80% will be cured.…”
Section: How Should Ais Detected On Biopsy Be Managed? How Should Patmentioning
confidence: 99%